Pancreaticogastrostomy as a choice of reconstruction after pancreaticoduodenectomy: a hospital based observational study - Reddy, Hetish M.; Bagree, Rajendra; Panwar, Pradeep; Jalendra, Gaurav (International Surgery Journal, 2021)
Background: The aim of this study was to compare the rate of occurrence of post-operative pancreatic fistulae (POPF) and other complications with pancreaticogastrostomy (PG) or pancreatojejunostomy (PJ) as a choice of reconstruction in classic Whipple’s Procedure. Methods: A hospital based prospective observational study collected data of 60 patients who underwent Whipple’s procedure from June 2018 to august 2019, in two different surgical units, where one-unit preferred PG as routine while the other unit preferred PJ. Results: Two out of 30 patients who underwent PG (Group A) developed POPF while Nine out of 30 patients who underwent PJ (Group B) developed POPF (p-value = 0.04) indicating a significant difference in outcome. The duration of hospital stay (DOHS) in our study in Group A was 12.82±1.74 days when compared to Group B was 13.88±2.01 days (p-value = 0.042). Conclusions: Our results indicate that the preferred reconstruction after classic Pancreaticoduodenectomy should be Pancreaticogastrostomy, but further validation with randomized control trials or multicenter studies with larger sample size are required.